2005
DOI: 10.1021/ja050886c
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic Metallofoldamers as Electrochemically Responsive Molecules

Abstract: Described are the design, synthesis, and study of nonbiological molecules based on salophen and salen ligands that fold into single-stranded helices in the presence of either Ni(II) or Cu(II). X-ray diffraction studies show that the materials fold into helical structures in the solid state, and a series of NMR studies provide strong evidence that the folded structures are conserved in solution. Metal coordination is required for folding, as NMR and X-ray show that the free ligands do not adopt helical structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(37 citation statements)
references
References 40 publications
0
33
0
3
Order By: Relevance
“…[6] "Helicates", molecules that template an abiotic helix, have been broadly investigated and reviewed. [1,7] This field includes short single-stranded oligopyridines, oligo(m-phenyleneethynylene) and zinc bilinones, all fold into helices upon coordination to metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…[6] "Helicates", molecules that template an abiotic helix, have been broadly investigated and reviewed. [1,7] This field includes short single-stranded oligopyridines, oligo(m-phenyleneethynylene) and zinc bilinones, all fold into helices upon coordination to metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the 1,2-disubstituted ethylene bridge in the chiral salen unit facilitated the synthesis of dynamic helical structures in which the preferred helicity is rationally predicted from the structure of the organic framework. In addition to the oligo(salamo) helical structures reported in this article, there have already been a number of reports on various kinds of helical structures based on the monomeric [31][32][33][34][35][36][37][38][39][40][41], dimeric [42,43] and polymeric [44][45][46] salen-type ligands, as well as the tris(saloph) triple-helical cages [93,94] and single-helix with different types of donor sets [90,[95][96][97]. It has already been demonstrated that the oligo(salamo) helical complexes show unique physical properties and reactivities [98][99][100][101], and the dynamic helicity control would be useful for switching of the chiroptical properties of the helical structures.…”
Section: Discussionmentioning
confidence: 97%
“…As one of the possible candidates of dynamic helical complexes, we designed metal complexes having a series of acyclic oligo(salen)-type ligands (H 2 salen = N,N'-disalicylideneethylenediamine) ( Figure 5a) [25][26][27][28][29][30], while there are several types of related helical structures based on monomeric [31][32][33][34][35][36][37][38][39][40][41], dimeric [42,43] and polymeric [44][45][46] salen-type ligands. We employed salamo derivatives, the oxime analog of salen, as the constituent of the oligomers (H 2 salamo = 1,2-bis(salicylideneaminooxy)ethane) [47,48].…”
Section: Molecular Designmentioning
confidence: 99%
“…The coordination number, change, and geometry of redoxactive metals enable the metal center to serve as a hub for electron-mediated, dynamic structural changes of metallopeptides, in light of previous examples of metal-mediated structure controls using catenane, 50 rotaxane, 51 helicate, 52,53 and rotor. 54 Arora, Canary, et al synthesized a new 17-residue peptide, Ac-SIRKLEYEIEELRLRIG-NH 2 , 25 with a view to realizing ¡-helix-to-¢-sheet transition by redox-active Cu ions.…”
Section: ç Redox-responsive Metallopeptidesmentioning
confidence: 99%